2011
DOI: 10.1002/anie.201104053
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Trifluoromethylation of Unactivated Olefins

Abstract: Activating the inactive: A copper‐catalyzed allylic trifluoromethylation of unactivated terminal olefins proceeds under mild conditions to produce linear allylic trifluoromethylated products with high E/Z selectivity (see scheme). The reaction can be applied to a range of substrates bearing numerous functional groups. Furthermore, the reaction is scalable and amenable to a benchtop setup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 403 publications
(91 citation statements)
references
References 59 publications
3
86
0
2
Order By: Relevance
“…In 2011, the groups of Buchwald 23 and Wang 24 showed that Togni's reagents can be used as a clean source of the CF 3 radical for the trifluoromethylation of alkenes. These trifluoromethylations rely on Cu(I) catalysis, and experimental evidence for the involvement of free CF 3 radicals was provided (Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, the groups of Buchwald 23 and Wang 24 showed that Togni's reagents can be used as a clean source of the CF 3 radical for the trifluoromethylation of alkenes. These trifluoromethylations rely on Cu(I) catalysis, and experimental evidence for the involvement of free CF 3 radicals was provided (Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
“…A proposed mechanism for this trifluoromethylation reaction is depicted in Scheme 3. Reaction of Togni's reagents with a copper catalyst generates a CF 3 radical (Scheme 2), 23,24 followed by radical addition and single-electron oxidation to give intermediate C. 26 Subsequent trapping of the carbocation C with a nucleophile leads to the desired product D. It is assumed that trifluoromethylation of olefin substrate E might be achieved using a copper-based strategy involving the generation of an allylic radical and a subsequent CF 3 transfer (Scheme 3, Path A). [27][28][29] Alternatively, if Togni's reagent 1 could be used as an electrophilic CF 3 ·equivalent, the final product F may be generated through an atom transfer radical addition type pathway (Scheme 3, Path B).…”
Section: Methodsmentioning
confidence: 99%
“…该反应将邻羟 基取代苯乙烯的 C-O 偶联与氟代芳环的 C-H 键活化 反应组合, 用以制备不同的 2-(多氟代苯)苯并呋喃衍生 物(25) [20] . 氟烷基是很多药物和天然产物中的重要结构基团, 最近 Loh 等 [21] 报道了首例亚铜催化的烯酰胺的直接 C-H 键活化三氟甲基化反应(Scheme 3), 为有机底物的氟 烷基化反应 [22] 提供了新思路. 该反应的官能团耐受性 运用该方法, 他们 [24] 成功合成了一种荧光染料 43 (Eq.…”
Section: Methodsunclassified
“…In view of the importance of trifluoromethylated olefins and alkynes, several groups have recently developed efficient methodologies for the direct trifluoromethylation of unactivated olefins and alkynes. Buchwald [15] followed by Wang [16] described the Cu-catalyzed trifluoromethylation of terminal olefins by using the Togni electrophilic trifluoromethylation reagent. Using Umemoto's reagent and catalyzed by (thiophene-2-carbonyloxy)copper in the presence of 2,4,6-collidine, Liu and co-workers [17] reported another method for the trifluoromethylation of terminal alkenes.…”
Section: Introductionmentioning
confidence: 99%